Solving of optimization hydrodynamic problems using the distributed computing resources of Moscow University - Zhumatiy, S.A.; Sobolev, S.I.; Stefanov, K.S. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
A software package architecture for solving the optimization problems of aero- and hydrodynamics in distributed computing environments is considered. The package consists of the FlowVision system for solving the hydrodynamic direct problems, the IOSO system for searching an optimal, and the X-Com system for distributing the computing loads on the nodes of supercomputers.